The Hidden Danger in Family Environment: The Role of Self-Reported Parenting Style in Cognitive and Affective Empathy Among Offenders - Wang, Shaishai; Hu, Huagang; Wang, Xinyang; Dong, Bo; Zhang, Tianyang (Frontiers in Psychology, 2021)
Parenting styles are considered to have an important influence on the development of individuals and have been associated with empathy. The present study aimed to investigate the self-reported different parenting style factors in childhood and adolescence and associated cognitive and affective empathy among offenders. Men incarcerated in prison in Jiangsu Province in China were invited to participate. Each consenting participant was asked to complete the Parental Bonding Instrument to collect information regarding the parenting styles they experienced in childhood and adolescence and the Interpersonal Reactivity Index to evaluate their empathy. A multivariable linear regression analysis was conducted to explore the associations between different parenting style factors and the empathy of offenders, and a one-way multivariate analysis of variance and a t-test were used to explore the differences in cognitive and affective empathy with different degrees of parenting style factors. The parental care and control factors in childhood and adolescence were significantly more strongly associated with empathy among offenders than the parental encouragement factor. There were different associations between the parental care and control factors and offenders’ empathy depending on whether the parenting styles were consistent or inconsistent. When the parenting styles were consistent, different degrees of parental care had a significant predictive effect on cognitive and affective empathy, while different degrees of parental control were only significantly associated with affective empathy among the offenders. When the parenting styles were inconsistent, different degrees of paternal and maternal control were associated with cognitive and affective empathy among the offenders. Our findings suggest that not only different parenting style factors experienced in childhood and adolescence had different predictive effects on empathy among offenders but also the degrees of parenting style factors and whether the paternal and maternal parenting styles were consistent or inconsistent may affect the patterns of parenting styles and empathy. Moreover, the parental control factor had a particular influence on empathy among the offenders. Our findings underscore the pressing need for adopting preventive monitoring measures or developing policies to improve parenting styles.